CHARACTER TRANSFORMATION IN THE GAME MOBILE LEGENDS: BANG BANG! (MLBB) AND ITS IMPACT - Irwanto, Benediktus Rengga; Wuryandari, Nurni Wahyu (Bambuti, 2023)
Chinese culture thrives on a lot of popular culture including gaming. One of the games that contain Chinese culture is Mobile Legends: Bang Bang! or MLBB, developed by Moonton as the developer company from Shanghai. Moonton elevates Chinese culture in MLBB through hero characters that gamers can choose from. There are 11 hero characters with Chinese culture, including the hero characters Chang'e, Sun, and Zilong who have the highest popularity. The three hero characters are based on mythical, literature and historical characters related to China, namely: (1) the mythical figure Chang'e as the hero character Chang'e, (2) the literature figure Sun Wukong as Sun, and (3) the historical character Zhao Yun as the hero character Zilong. The hero characters have undergone transformation from the name to the story background so there are differences from the figures. This transformation aims to be an adjustment to the game conceptualization as well as a marketing strategy to attract the players’ attention. This research will examine the figures’ transformation into selected MLBB hero characters (Chang'e, Sun, and Zilong), and it is concluded that the transformations made by the developers not only attract the players’ attention, but also eventually became MLBB's strategy to develop the market.